Peran Guru dalam Meningkaatkan Minat Belajar Siswa menggunakan Metode Resitasi dan Metode Diskusi pada Mata Pelajaran PPKn di SMP Negeri 37 Medan T.A 2021/2022 - Dewi Lestari Pardede; Lukman Pardede; Monalisa Siahaan; Alim Parangin-angin; Rina Devi Romauli Siahaan (Departement of Mathematics Education, 2023)
This study aims to determine the teacher's role in increasing student interest in learning using the recitation method and the discussion method on PPKn subjects at UPT SMP Negeri 37 Medan in the 2021/2022 academic year. This type of research is a type of quantitative descriptive research. The population in this study were seventh grade students of SMP Negeri 37 Medan in the academic year 2021/2022. The results showed that the teacher's role was positively and significantly related to students' interest in learning, which indicated that the t count > t table (49.41 > 12.02) and the significant value < a (0.00 < 0.05).